2018
DOI: 10.1002/14651858.cd012406.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide antibiotics for bronchiectasis

Abstract: Long-term macrolide therapy may reduce the frequency of exacerbations and improve quality of life, although supporting evidence is derived mainly from studies of azithromycin, rather than other macrolides, and predominantly among adults rather than children. However, macrolides should be used with caution, as limited data indicate an associated increase in microbial resistance. Macrolides are associated with increased risk of cardiovascular death and other serious adverse events in other populations, and avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
11

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 65 publications
2
57
0
11
Order By: Relevance
“…Furthermore, in a very recent Cochrane review from January 2018, including adults and children with non‐CF bronchiectasis, authors concluded that long‐term macrolide therapy may reduce the frequency of exacerbations and improve quality of life. Evidence was mainly derived from studies of azithromycin, rather than other macrolides, and predominantly among adults rather than children …”
Section: The Role Of Macrolides In Non‐cf Bronchiectasismentioning
confidence: 99%
“…Furthermore, in a very recent Cochrane review from January 2018, including adults and children with non‐CF bronchiectasis, authors concluded that long‐term macrolide therapy may reduce the frequency of exacerbations and improve quality of life. Evidence was mainly derived from studies of azithromycin, rather than other macrolides, and predominantly among adults rather than children …”
Section: The Role Of Macrolides In Non‐cf Bronchiectasismentioning
confidence: 99%
“…Macrolides have important adverse effects including direct side effects, population risk of antimicrobial resistance, induction of resistance in NTM, cardiovascular effects and drug-drug interactions. 8 The results of safety evaluation of the 3 trials included in our meta-analysis are extensively reported in the primary publications and subsequent meta-analyses and so were not the focus of this manuscript. This said, the trend to worse QoL in younger patients with non-frequent exacerbations (Fig 2), may very well be a reflection of more side effects in this particular subgroup, which would be consistent with the clinical experience of the authors.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…7 Macrolide antibiotics are among the most widely used chronic treatments to prevent exacerbations in bronchiectasis. 8,9 They are particularly attractive because there is evidence they target each of the key components of bronchiectasis pathophysiology. In addition to reducing bacterial burden, they have well established immunomodulatory effects which include suppression of neutrophil mediated lung damage, and they also enhance cilia function to promote mucociliary clearance.…”
Section: Introductionmentioning
confidence: 99%
“…In a carefully observed case series in Respirology , Martin et al describe the clinicopathological features of patients with idiopathic chronic productive cough and report a favourable response to low‐dose, long‐term azithromycin, as well as some indicators of response. In doing so, they place this syndrome within the larger context of the macrolide‐responsive neutrophilic bronchitis that we recognize in bronchiectasis, chronic obstructive pulmonary disease (COPD), bronchiolitis and some forms of asthma …”
mentioning
confidence: 99%